2014
DOI: 10.1016/j.bbmt.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Second Solid Cancers after Allogeneic Hematopoietic Cell Transplantation Using Reduced-Intensity Conditioning

Abstract: We examined risk of second solid cancers after allogeneic hematopoietic cell transplantation (AHCT) using reduced intensity/non-myeloablative conditioning (RIC/NMC). RIC/NMC recipients with leukemia/myelodysplastic syndrome (MDS) (n=2833) and lymphoma (n=1436) between 1995–2006 were included. In addition, RIC/NMC recipients 40–60 years of age (n=2138) were compared with patients of the same age receiving myeloablative conditioning (MAC, n=6428). The cumulative incidence of solid cancers was 3.35% at 10-years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
4
52
0
2
Order By: Relevance
“…3,5,11,12 Reports describing skin cancer following HCT are dominated by case reports, but at least five large studies have reported an increased incidence of melanoma after allogeneic HCT compared with the general population (SIR 1.4–8.3). 3,5,1113 The risk of developing melanoma was also increased compared with the general population after HCT with reduced-intensity conditioning (RIC) regimens (SIR 3.04 for leukemia or myelodysplastic syndrome patients and SIR 3.52 for lymphoma patients). 13 An Asian study reported an increased incidence of skin cancers without distinguishing cancer subtypes after allogeneic HCT (SIR 7.2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3,5,11,12 Reports describing skin cancer following HCT are dominated by case reports, but at least five large studies have reported an increased incidence of melanoma after allogeneic HCT compared with the general population (SIR 1.4–8.3). 3,5,1113 The risk of developing melanoma was also increased compared with the general population after HCT with reduced-intensity conditioning (RIC) regimens (SIR 3.04 for leukemia or myelodysplastic syndrome patients and SIR 3.52 for lymphoma patients). 13 An Asian study reported an increased incidence of skin cancers without distinguishing cancer subtypes after allogeneic HCT (SIR 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…3,5,1113 The risk of developing melanoma was also increased compared with the general population after HCT with reduced-intensity conditioning (RIC) regimens (SIR 3.04 for leukemia or myelodysplastic syndrome patients and SIR 3.52 for lymphoma patients). 13 An Asian study reported an increased incidence of skin cancers without distinguishing cancer subtypes after allogeneic HCT (SIR 7.2). 14 One study reported that the cumulative incidences of BCC and SCC were 6.5% and 3.4% at 20 years after allogeneic HCT in a predominantly Caucasian cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer follow-up is also needed to understand the full risks of secondary cancers after RIC regimens. 83 The comparison of risks of secondary malignancy after RIC or MAC remains inconclusive but the incidence of this complication may become clearer after a longer follow-up. 82 Other common, serious complications of HCT, particularly for men and women in their reproductive years, are hypogonadism and infertility.…”
Section: Long-term Complicationsmentioning
confidence: 99%